Optimal design of a variable stiffness joint in a robot manipulator using the response surface method - Yoo, Jeonghoon; Hyun, Myung Wook; Choi, Jun Ho; Kang, Sungchul; Kim, Seung-Jong (KOREAN SOC MECHANICAL ENGINEERS, 2009)
The response surface method combined with the design of experiment-based design optimization of a variable stiffness joint (VSJ) is presented in this article. A VSJ used in a manipulator of a robot arm to support 1 kg payload at the end is designed by considering the minimization of the total weight as the objective function. Owing to the requirement of large rotational stiffness of the VSJ, over 10 N center dot m, ring-type permanent magnets are adopted. First, a model composed of two permanent magnets was initially manufactured and tested for comparison with the analysis results. Then, a three-ring-type permanent magnet-based model is suggested and optimized to increase the torque of VSJ. The finite element method is used as a magnetic field analysis method to substitute for the expensive experimental process. Optimization results decrease the weight from 0.899 kg to 0.538 kg, still satisfying the requirement for the rotational stiffness.
Keywords: FORCE